2017
DOI: 10.4174/astr.2017.93.6.305
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic reinforcement suture on staple-line of duodenal stump using barbed suture during laparoscopic gastrectomy for gastric cancer

Abstract: PurposeDuodenal stump fistula (DSF) is a serious complication after gastrectomy for gastric cancer. Although risk evaluation and management of DSF were presented by some investigators, there was no technical attempt has been made to prevent DSF during laparoscopic gastrectomy until now.MethodsConsecutive 99 patients were enrolled from April 2014 to February 2016 in 2 institutes. All patients were performed laparoscopic gastrectomy for gastric cancer. After cutting of duodenal stump, laparoscopic reinforcement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The LRS method and single purse-string sutures [33]spent approximately equal time on the reinforcement of the duodenal stump. Besides, it was approximately the average time of reinforcement of duodenal stump, including barbed suture [34], lambert suture [35], and two half-purse-string sutures [36]. However, these methods require multiple stitches and knots, which is rather difficult for inexperienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The LRS method and single purse-string sutures [33]spent approximately equal time on the reinforcement of the duodenal stump. Besides, it was approximately the average time of reinforcement of duodenal stump, including barbed suture [34], lambert suture [35], and two half-purse-string sutures [36]. However, these methods require multiple stitches and knots, which is rather difficult for inexperienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the surgical techniques and many other local factors, including the insufficient blood supply, the tissue vulnerability, such as local edema and scar on duodenal wall, the length of duodenal stump, and high pressure inside duodenal cavity might influence the healing of duodenal stump and result in DSL (6). So, in order to prevent DSL, reinforcement of duodenal stump is necessary and some reinforcement methods have been applied widely, including barbed suture (12), Lembert suture (13), two half-purse-string sutures (14). However, these methods require multiple stitches and knots, which is rather different for the unexperienced surgeons (12–14).…”
Section: Discussionmentioning
confidence: 99%
“…So, in order to prevent DSL, reinforcement of duodenal stump is necessary and some reinforcement methods have been applied widely, including barbed suture (12), Lembert suture (13), two half-purse-string sutures (14). However, these methods require multiple stitches and knots, which is rather different for the unexperienced surgeons (12–14). This study was a retrospective, one-arm clinical trial focusing on a new maneuver, single purse-string suture, for reinforcement of duodenal stump in patients harboring gastric adenocarcinoma following laparoscopic radical gastrectomy with Roux-en-Y or BillrothIIreconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the staple line of duodenal stump should be reinforced by intracorporeal suture to prevent the duodenal stump fistula. Recently, it is reported that the method using barbed suture can be performed in a short operation time without any technical difficulties [22] .…”
Section: Cutting the Duodenummentioning
confidence: 99%